Analysis Of Robusta Coffee Supply Chain Through The Food Supply Chain Network Approach - Timbul Rasoki; Ana Nurmalia (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2021)
Rejang Lebong Regency is the producer center of robusta coffee in Bengkulu, the production continues to increase. Robusta coffee marketing in Rejang Regency is generally interesting because most of the sales objectives of robusta coffee from farmers are to coffee processing companies, both inside and outside the province. It’s suspected that there are variations in the production of robusta coffee in Rejang Lebong Regency, so that robusta coffee business actors have different marketing channels according to the limited supply they have. Based on the results of the research on 37 people who were selected by purposive sampling and through the Food Supply Chain Network (FSCN) approach, the robusta coffee supply chain conditions were running smoothly. This can be seen from the integration or cooperation between supply chain actors that have been established, especially with the coffee processing industry. There are 3 marketing channels for Robusta coffee in Rejang Lebong Regency and can assess the performance of its supply chain. Through the analysis of the marketing margin and the farmer's share shows that the Robusta coffee supply chain on channel 3 is more efficient than channel 1 and channel 2 because it has the lowest margin and the highest share of farmers.